Value-based management with corporate social responsibility - Martin, John D., 1945-; Petty, J. William, 1942-; Wallace, James S. (New York ; Oxford : Oxford University Press, 2009)
The current financial crisis has caused many of us to question the motives and actions that drive the business world, even the basic notion that firms should be run so as to maximize shareholder value has come under increasing scrutiny.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Value analysis (Cost control); Industrial management